Photocurable resins for 3D printing: chemical and materials engineering aspects - Pietraszewski, Jakub; Topa-Skwarczyńska, Monika; Noworyta, Małgorzata; Ortyl, Joanna (Chemical and Process Engineering: New Frontiers, 2026)
The development of functional photopolymer resins for additive manufacturing requires a combined materials and chemical engineering approach that addresses both resin formulation and the interactions between photocurable systems and 3D printing technologies. Herein, a series of investigations was conducted to rigorously delineate the influence of titanium dioxide (TiO2) as an additive on the kinetics of the photopolymerization process and on the resulting quality parameters of photocurable resin prints. TiO2 was incorporated at concentrations of 0.1–30 wt.%, and the resins were studied using Real-Time FT-IR, photo-DSC, photo-rheology and Jacobs curves. Low-to-medium additive concentrations accelerated early polymerization due to enhanced light scattering, whereas higher concentrations reduced light penetration and delayed curing. In addition to material performance, the chemical engineering aspects of additive manufacturing were examined by fabricating printouts on two 3D printers employing different technologies. Printouts from two 3D printers with different technologies, LCD and DLP, revealed a strong dependence on printer technology: the LCD system successfully printed only the base and 0.1 wt.% TiO2 formulations, but with higher quality, while the higher-intensity DLP system processed all formulations. These results demonstrate that both titanium dioxide content and printing technology influence curing efficiency and final print quality, which are critical for the development of photopolymer resins.